Kadar gula darah atlet sepak bola remaja setelah pemberian diet beban glikemik - Rahma Wati Dwi Lestari; Deny Yudi Fitranti; Nurmasari Widyastuti; Ahmad Syauqy; Binar Panunggal; Fillah Fithra Dieny; Hartanti Sandi Wijayanti; Dewi Marfu'ah Kurniawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Effect of diets with glycemic load arrangement on blood glucose levels in young soccer athletes Background: Carbohydrate arrangement considering the glycemic index (GI) and glycemic load (BG) are important to support the performance of athletes.Objective: To examine the effect of diets with glycemic load arrangement on blood glucose levels in young soccer athletes.Methods: Quasi-experimental study on 14 male young soccer players aged 15-18 years old at Terang Bangsa Soccer School. Each subject completed 4 trials separated by at least 7 days as a washout period. Diets provided consist of high GI with high GL diet (H-H), low GI with high GL diet (L-H), high GI with low GL (H-L), and low GI with low GL diet (L-L). Collected data were fasting blood glucose level (BGL 0), blood glucose level one hour after intervention (BGL 1), blood glucose level two hours after intervention (BGL 2), and blood glucose level after exercise (BGL 3).Results: The results of paired t-test analysis showed that there were differences between fasting blood glucose level and blood glucose level one hour after intervention, blood glucose level one hour after intervention and blood glucose level two hours after intervention, blood glucose level two hours after intervention and blood glucose level after exercise in the H-H and L-H diet group. In the L-L diet group, there were differences between BGL 2 and BGL 3. One-Way ANOVA analysis showed that there were no significant differences in blood glucose levels one hour after the intervention, blood glucose level two hours after intervention, and blood glucose level after exercise between groups.Conclusions: High glycemic load diets influence the increase in blood glucose levels at 1 hour postprandial and after exercise. Low glycemic load diets influence the increase in blood glucose levels after exercise. Diets with the arrangement of glycemic index and glycemic load did not affect blood glucose levels between diet groups.